Evaluation of the diagnostic accuracy of lower urinary tract symptoms (LUTS) in uncomplicated UTI in Pakistani women - NIAZ, WAQAR; Yasmeen, Haleema; Shamsher, Saadia (Journal of the Pakistan Medical Association, 2024)
Objective: To evaluate the diagnostic accuracy of lower urinary tract symptoms in uncomplicated urinary tract infection in women. Method: The cross-sectional study was conducted from September 2020 to December 2021 after approval from the ethics review board of Jinnah Postgraduate Medical Centre, Karachi, and comprised data of women aged at least 16 years from 8 institutions across Pakistan. Data included menstruation status, symptoms, urinalysis and organisms found in urine samples. The association of urinalysis variables with symptoms among culture-positive patients was measured to assess the certainty of positive diagnosis. Data was analysed using SPSS 23. Results: Of the 457 women with mean age 37.87±13.9 years, 182(39.8%) had a positive urine culture. Dysuria was the most significant symptom 120(65.9%), followed by daytime frequency 114(62.6%) amongst culture-positive patients. On urinalysis, 139(76.3%) had white blood cells, and 66(36.2%) had haematuria. Dysuria along with the presence of leucocyte esterase had the highest diagnostic utility (p=0.002). Urgency along with haematuria was strongly predictive of urinary tract infection (p=0.058). Conclusion: The diagnosis of uncomplicated urinary tract infection in women could be reliably made based on a combination of symptoms along with urine analysis without urine culture. Key Words: Urinary tract infection, Lower urinary tract symptoms, Urinalysis; Urine culture.